Tectonostratigraphy and Structures of Eastern Seram - Bachri, Syaiful (Indonesian Journal on Geoscience, 2011)
DOI:Â 10.17014/ijog.v6i2.118The eastern Seram is part of the Outer Banda Arc consisting of para-autochthonous and allochthonous units which are unconformably overlain by the autochthonous units. The para-autochthonous units are derived from the outer margin of the Australian NW Shelf. This sequence comprises Permian metamorphic rocks of the Kobipoto Complex and its cover of Triassic - Jurassic to Cretaceous - Tertiary age. The allochthonous unit, or the pre-collisional Banda fore-arc sequence was overthrusted onto the NW Shelf sequence. The sedimentsÂ overlying unconformably the allochthonous and para-autochthonous units are referred to as autochthonous units. These autochthonous units comprise sediments deposited post-Neogen collisional event between the Australian Continent and the Banda subduction zone. Structures develop in the eastern Seram are thrust, normal faults, folds, and cleavages. The thrusts are verging to the northeast suggesting that the deformation occurred before Seram was rotated in an E-W direction.